Drought severity in intensive agricultural areas by means of the EDI index - PROCHÁZKOVÁ, Petra; CHUCHMA, Filip; STŘEDA, Tomáš (Contributions to Geophysics and Geodesy, 2016)
The aim of this work was the evaluation of drought severity development in the Czech Republic for the period 1971–2015 by the means of the Effective Drought Index (EDI). Annual values of the EDI index were determined using the method of effective precipitation for 14 localities spread throughout the Czech Republic (Central Europe). The seven categories were created according to obtained index values for the drought conditions determination for years during the period 1971–2015 through the percentile method. The annual index values were compared with acquired 2nd, 15th, 45th, 55th, 85th and 98th percentiles. Both the years with precipitation unfavourable conditions: 1972, 1973, 1984, 1990, 1991, 1992, 1993 and 2015 and the years with precipitation favourable conditions: 1977, 1987, 1995, 2001, 2002 and 2010 were determined. Precipitation conditions in the growing season from 61st to 180th day of the year were also analysed. This evaluation was conducted during the period 1971–2015 through the ten-day index values which were compared with acquired 2nd, 15th, 45th, 55th, 85th and 98th percentiles. Dry growing seasons occurred in 1973, 1974, 1976 and 1993. Wet growing seasons occurred in 1987, 2006 and 2010. Trend analysis of annual index values was performed through the Mann-Kendall test. Highly statistically significant increasing linear trends (P < 0.01) were found for four localities (Uhersk´y Ostroh, Vysok´a, Znojmo-Oblekovice and Žatec); statistically significant increasing trends (P < 0.05) were found for three localities (Brno-Chrlice, Lednice and Lípa). Based on the extrapolation of the trend, a slightly higher effective precipitation can be expected during the year in a substantial part of the country. However, these findings do not necessarily mean an optimal supply of agricultural land with water. Precipitation exhibits considerable unevenness of distribution through time. Given the increasing evapotranspiration demands of the environment their availability is limited.